Super-frog saves Tokyo - Murakami, Haruki (Harvill ; Replika press, 2025)
Katagiri found a giant frog waiting for him in his apartment. It was powerfully built, standing over six feet tall on its hind legs. A skinny little man no more than five foot three, Katagiri was overwhelmed by the frog's imposing bulk. 'Call me 'Frog,'' said the frog in a clear, strong voice. Katagiri stood rooted in the doorway, unable to speak. 'Don't be afraid. I'm not here to hurt you. Just come and close the door. Please.' Briefcase in his right hand, grocery bag with fresh vegetables and canned salmon cradled in his left arm, Katagiri didn't dare move. 'Please, Mr. Katagiri, hurry and close the door, and take off your shoes.'